2004
DOI: 10.1128/jb.186.13.4209-4217.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Functional Relationships among the Nontypeable Haemophilus influenzae HMW Family of Adhesins

Abstract: Nontypeable Haemophilus influenzae (NTHi) is a common cause of localized respiratory tract disease and initiates infection by colonizing the nasopharynx. Approximately 75 to 80% of NTHi clinical isolates produce proteins that belong to the HMW family of adhesins, which are believed to facilitate colonization. The prototype HMW adhesins are designated HMW1 and HMW2 and were identified in NTHi strain 12. HMW1 and HMW2 are 71% identical and 80% similar overall, yet display differing cellular binding specificities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 41 publications
(36 reference statements)
2
80
0
Order By: Relevance
“…HMWA is the structural component of the adhesin, HMWB has a role in transmembrane translocation, and HMWC is required for glycosylation of HMWA (7,9,37,110). Similarly, strain 86-028NP's two HMW gene clusters contain homologues of the hmwA, hmwB, and hmwC genes in the same gene context as in strain 12 (16). The HMW1A and HMW2A proteins from Hap is an autotransported protein with a domain homologous to the catalytic domain of immunoglobulin A1 proteases.…”
Section: Resultsmentioning
confidence: 99%
“…HMWA is the structural component of the adhesin, HMWB has a role in transmembrane translocation, and HMWC is required for glycosylation of HMWA (7,9,37,110). Similarly, strain 86-028NP's two HMW gene clusters contain homologues of the hmwA, hmwB, and hmwC genes in the same gene context as in strain 12 (16). The HMW1A and HMW2A proteins from Hap is an autotransported protein with a domain homologous to the catalytic domain of immunoglobulin A1 proteases.…”
Section: Resultsmentioning
confidence: 99%
“…(4). Moreover, on the basis of the lengths of the amplified fragments, complete hmw1A-like and hmw2A-like genes were very likely present.…”
Section: Vol 74 2006 Variation In H Influenzae Hmw Binding Domainsmentioning
confidence: 99%
“…With a few exceptions, our results clearly showed clustering into HMW1-like and HMW2-like groups, in agreement with the hmw1A-like and hmw2A-like encoding genes. Recently, Buscher et al demonstrated that the chromosomal location of the hmw1A and hmw2A genes does not necessarily correlate with the binding phenotype of the associated adhesins, since, in some isolates, the hmw1A gene encodes a protein with HMW2 adherence properties and vice versa (4). In the present study, no investigation was conducted on the actual adherence properties of the hmw1A and hmw2A gene products to human ephithelial cells, our main object being to characterize hmwA alleles from several clinical NTHi isolates by assessing conservation and diversity at sequence level.…”
Section: Vol 74 2006 Variation In H Influenzae Hmw Binding Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two products were not clearly resolved by gel electrophoresis, so the lack of one hmw locus would not have been detected. Both hmw and hia are known to differ in sequence from strain to strain (4,33). We did not attempt to assess the sequence heterogeneity of these loci; rather the internal primers that we used were selected to hybridize with conserved regions of the hia and hmwA sequences.…”
Section: Phylogenetic Analysis (I) Mlstmentioning
confidence: 99%